Lexica afroasiatica vi - Takács, Gábor (Lingua Posnaniensis, 2012)
Since we know little about the Proto-Afro-Asiatic vowel system, the proposed list of the reconstructed Proto-Afro-Asiatic forms is arranged according to consonantal roots (even the nominal roots). Sometimes, nevertheless, it was possible to establish the root vowel, which is given in the paper additionally in brackets. The lexical parallels suggested herein, are based on the preliminary results in reconstructing the consonant correspondences achieved by the Russian team of I.M. Diakonoff (available in a number of publications4) as well as on my own observations refining the Russian results (most importantly Takács 2001). The most important results can be summarized as follows. The labial triad *b - *p - *f remained unchanged in Egyptian, South Cushitic, and Chadic, while the dental series *d - *t - *s was kept as such by Semitic and South Cushitic (AA *s continued as *T in Berber, Cushitic and Chadic, and it was merged into t vs. d in Egyptian). The fine distinction of the diverse sibilant affricates and spirants (AA *c, *μ, *@, *s, *D, *¸, *E, *b, *ĉ, *H, *ŝ) was best preserved in Semitic, South Cushitic and West Chadic (while some of these phonemes suffered a merger in other branches and groups). The Russian scholars assumed a triad of postvelar (uvulear) stops with a voiceless spirant counterpart: *-, *", *q, and *¯, the distinction of which was retained in Cushitic and Chadic, but was merged into *¯ in Semitic and Egyptian. In a number of cases, however, it is still difficult to exactly reconstruct the root consonants on the basis of the available cognates (esp. when these are from the modern branches, e.g., Berber, Cushitic-Omotic, or Chadic). In such cases, the corresponding capitals are used (denoting only the place of articulation).